Observations of Modified Warm Deep Water beneath Ronne Ice Shelf, Antarctica, from an Autonomous Underwater Vehicle - Davis, Peter E. D.; Jenkins, Adrian; Nicholls, Keith W.; Dutrieux, Pierre; Schröder, Michael; Janout, Markus A.; Hellmer, Hartmut H.; Templeton, Rob; McPhail, Stephen (Journal of Geophysical Research: Oceans, 2022)
Filchner-Ronne Ice Shelf (FRIS) is the world’s largest ice shelf by volume. It helps regulate Antarctica’s contribution to global sea level rise, and water mass transformations within the sub-ice-shelf cavity produce globally important dense water masses. Rates of ice shelf basal melting are relatively low, however, as the production of cold (-1.9°C) and dense High Salinity Shelf Water over the Weddell Sea continental shelf isolates the ice shelf from large-scale inflow of warm water. Nevertheless, a narrow inflow of relatively warm (-1.4°C) Modified Warm Deep Water (MWDW) that hugs the western flank of Berkner Bank is observed to reach Ronne Ice Front, although the processes governing its circulation and fate remain uncertain. Here we present the first observations taken within the ice shelf cavity along this warm water inflow using the Autosub Long Range autonomous underwater vehicle. We observe a core of MWDW with a south-westward velocity of 4 cm s-1 that reaches at least 18 km into the sub-ice cavity. The hydrographic properties are spatially heterogeneous, giving rise to temporal variability that is driven by tidal advection. The highest rates of turbulent dissipation are associated with the warmest MWDW, with the vertical eddy diffusivity reaching 10-4 m2 s-1 where the water column is fully turbulent. Mixing efficiency is close to the canonical value of 0.2. Modelling studies suggest MWDW may become the dominant water mass beneath FRIS in our changing climate, providing strong motivation to understand more fully the dynamics of this MWDW inflow.